Surgical repair of annulus defect with biomimetic multilamellar nano/microfibrous scaffold in a porcine model. (9th June 2017) - Kang, R.; Li, H.; Xi, Z.; Ringgard, S.; Baatrup, A.; Rickers, K.; Sun, M.; Le, D.Q.S.; Wang, M.; Xie, L.; Xie, Y.; Chen, M.; et al.
Abstract: Annulus defect is associated with reherniation and disc degeneration after discectomy; currently there is no effective treatment that addresses this problem. The annulus is a hierarchical lamellar structure, where each lamella consists of aligned collagen fibres, which are parallel and tilted at 30° to the spinal axis. In this study, a biomimetic biodegradable scaffold consisting of multilamellar nano/microfibres, sharing nanotopography and microporosity similar to the native lamellar structure, was assessed in a porcine model, aided by sealing with fascia and medical glue and subsequent suture fixation. After 6‐ and 12‐week observation, we found that this treatment restored nucleus volume and slowed down disc degeneration, as indicated by magnetic resonance imaging of T1/T2‐weighted, T2‐mapping, T1‐ρ imaging. Histological analysis showed aligned collagen fibres organized in the scaffold and integrated with surrounding native annulus tissue. The autologous bone marrow concentrate‐seeded scaffolds showed slightly earlier collagen fibre formation at 6 weeks. This novel treatment could efficiently close the annulus defect with newly formed, organized and integrated collagen fibres in a porcine model. Copyright © 2016 John Wiley & Sons, Ltd.